Design and Deploy web sites with Macromedia® Dreamweaver® MX 2004 and Contribute® 3 : Training from the Source - Lowery, Joseph (Adobe Press, 2004)
Tired of watching your elegantly constructed Web sites dissolve into a jumble of disorganized pages, broken links, and badly written code as they're updated and added to over time? Then get this guide and regain control by learning to design and deploy Dreamweaver sites specifically for use with Macromedia's hot, new content-management tool Contribute. In the first Macromedia-authorized book to cover this natural pairing, veteran author Joseph Lowery shows you how to develop Dreamweaver Web sites that anyone can update and maintain via Contribute. Through a series of project-based tutorials, Joseph shows you how to take advantage of the programs' shared check-in/check-out and versioning systems, integrated administration, and myriad other complementary features to create sophisticated, unbreakable sites that are a breeze for content creators and administrators alike. You'll also find lessons on handling server-side includes, establishing CSS guidelines, working with external documents, creating and using templates, and more! A companion CD includes all the lesson files you'll need to complete the book's projects. ** Please note: The lessons in the book-and their accompanying files-build upon one another. The basic files are contained in Lesson 2 which, as instructed, are used to create the basic Dreamweaver site. Each subsequent lesson's files are copied on top of the site; the lesson files are stored in the appropriate folders to make copying a one-step operation.